The application of think pair share cooperative learning strategies to improve English learning outcomes in elementary schools - Rizka Afni Amalia; Mela Rafika Yuliandari; Faustinina Kautsar (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to describe the activities of teachers and students, mastery of students'critical thinking skills, improve English learning outcomes through think pair sharecooperative learning strategies in elementary schools. The researcher found that thethinking skills of students were very lacking, this could be seen from the number ofstudents who could not respond to every statement made by the teacher. This study usesa quantitative descriptive method The object of research is the improvement of learningoutcomes which include learning outcomes of knowledge and skill competencies. Tomeasure the results of learning English, students used multiple choice learning outcomestests for knowledge learning outcomes and speaking skills tests to measure skills learningoutcomes given at the end of each cycle. It can be concluded that the use of learningstrategies that are in accordance with the type of TPS can further develop students'thinking skills in English subjects in elementary schools.